Effects of modified Portland cement and MTA on fibroblast viability and cytokine production - Gomes Filho, João Eduardo [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Dezan Junior, Eloi [UNESP]; Watanabe, Simone [UNESP]; Faria, Max Douglas [UNESP]; Gomes, Alessandra Cristina [UNESP]; Lodi, Carolina Simonetti [UNESP]; Oliveira, Sandra Helena Penha de [UNESP] (My University, 2012)
Objective: The aim of this study was to investigate the effects of a new Portland Cement formulation (CPM) comparing it to Angelus MTA on cell viability and IL-1β and IL-6 release by mouse fibroblasts. Methods: Polyethylene tubes filled with these materials were placed into 24-well cell culture plates with mouse fibroblasts. Empty tubes were used as control. After 24 hours, MTT assay was used to evaluate the cell viability. For cytokine assay, mouse fibroblasts were incubated in 24-well flat-bottom plates with set material disks at the bottom or without material, as control. After 24 hours, culture media were collected for cytokine evaluation by using ELISA. Results: CPM and Angelus MTA did not inhibit the cell viability. Both materials induced IL-6 and IL-1β release and the amount was statistically significant compared with the control group. Conclusions: Both materials were not cytotoxic in fibroblast culture and induced IL-6 and IL-1β release.
Keywords: Cytotoxicity; Dental materials; MTA